Liquid Biopsy in Rare Cancers: Lessons from Hemangiopericytoma. (7th March 2018) - Nicolazzo, Chiara; Colangelo, Luciano; Corsi, Alessandro; Carpino, Guido; Gradilone, Angela; Sonato, Chiara; Raimondi, Cristina; Gaudio, Eugenio; Gazzaniga, Paola; Gianni, Walter
Abstract : Hemangiopericytoma (HPT) is a rare mesenchymal tumor of fibroblastic type and for its rarity is poorly studied. The most common sites of metastatic disease in patients with intracranial HPT are the bone, liver, and lung, suggestive for an hematogenous dissemination; for this reason, we investigated, for the first time, the presence of circulating tumor cells (CTCs) in hemangiopericytoma patient by CellSearch® and SceenCell® devices. Peripheral blood samples were drawn and processed by CellSearch, an EpCAM-dependent device, and ScreenCell®, a device size based. We found nontypical CTCs by CellSearch system and the immunofluorescence analysis performed on CTCs isolate by ScreenCell demonstrated the presence of single CTCs and CTC clusters. The molecular characterization of single CTCs and CTC clusters, using antibodies directed against EpCAM, CD34, cytokeratins (8, 18, and 19), and CD45, showed a great heterogeneity in CTC clusters. We believe that the present study may open a new scenario in the rare tumors: the introduction of the liquid biopsy and the molecular characterization of circulating tumor cells could lead to personalized targeted treatments and also for rare tumors.